Maternal exposure of triclosan cause intrauterine development restriction, delay in puberty installation and deregulation of testicular function in rat offspring (Acta Scientiarum. Health Sciences, 2019)
This study aimed to evaluate the effects of maternal exposure to triclosan (TCS), during gestation and lactation on physical development, puberty installation and testicular function of male offspring in puberty and sexual maturity. Sixteen pregnant Wistar rats were used and divided into four experimental groups: GI- they received corn oil daily by gavage; GII- they received 75 mg kg-1 day-1 of TCS; GIII- they received 150 mg kg-1 day-1 of TCS and GIV- they received 300 mg kg-1 day-1 of TCS during pregnancy and lactation. The mean weight of the treated rat’s offspring was lower in comparison to GI group. In the exposed offspring. A delay in puberty installation was observed following the exposure to triclosan. Regarding to the stages of the seminiferous epithelium in puberty, it was noticed an increase of the I-VI stages in GIV group, compared with to GI. In sexual maturity, it was observed an increase of VII-VIII, IX-XIII in contrast to a reduction of XIV stage in treated animals, comparing to GI. There was no difference in the number of Sertoli cells. We conclude that the maternal exposure to TCS during gestation and lactation causes restriction of the intrauterine development, delay in the puberty installation and deregulation in the seminiferous epithelium cycle.